Electrode active material and preparation method thereof, electrode, battery and device

By forming a coating layer of reaction products of sulfur-containing compounds and lithium-containing compounds on the surface of the nuclear material of the positive electrode active material of the lithium-ion battery, the problem of high DC impedance growth rate during the battery cycle is solved, and the battery cycle performance and specific capacity are achieved. promote.

CN115836406BActive Publication Date: 2025-02-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080102741.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-10
Publication Date
2025-02-21
Estimated Expiration
2040-09-10

AI Technical Summary

Technical Problem

The positive electrode active materials of existing lithium-ion batteries have a high DC impedance growth rate during the cycle process, which affects the cycling performance and life of the battery.

Method used

An electrode active material having a cladding layer is used, and the cladding layer of the material contains a reaction product of a sulfur-containing compound and a lithium-containing compound, and the reaction product contains Li, S and O elements. The material is prepared by applying a solution containing a cladding-forming material to the surface of the nuclear material and subjecting to heat treatment.

Benefits of technology

The DC impedance growth rate of the battery during the cycle is reduced, the cycling performance and specific capacity of the battery are improved, and the gas production is reduced, which improves the performance of the battery at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115836406B_ABST
    Figure CN115836406B_ABST
Patent Text Reader

Abstract

An electrode active material and a preparation method thereof, an electrode, a battery and a device. The electrode active material comprises: a core and a coating layer, wherein the core contains a ternary material, the coating layer covers the core, the coating layer contains a reaction product of a sulfur-containing compound and a lithium-containing compound, and the reaction product contains Li element, S element and O element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium secondary batteries, and in particular relates to an electrode active material and a preparation method thereof, as well as an electrode, a battery and a device. Background Art

[0002] Since their first commercialization, rechargeable lithium-ion batteries have been widely used in a variety of portable electronics as well as large-scale electric vehicles and energy storage grids.

[0003] Lithium-ion battery cathode active materials generally include lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium nickel cobalt aluminum oxide (NCA) and lithium nickel cobalt manganese oxide (NMC), etc. Lithium ions can be reversibly inserted and removed from the above cathode materials.

[0004] There is still a need in the art for electrode active materials with better performance. Summary of the invention

[0005] The present disclosure provides a novel electrode active material with a coating layer, wherein the coating layer contains a reaction product of a sulfur-containing compound and a lithium-containing compound, wherein the reaction product contains Li, S, and O. The electrode active material of the present disclosure is used in a battery, and the battery exhibits a reduced DC resistance (DCR) growth rate during a cycle.

[0006] In some aspects, the present disclosure provides an electrode active material having a coating layer, comprising:

[0007] core, the core contains ternary materials;

[0008] The coating layer covers at least a portion of the surface of the core, and the coating layer contains a reaction product of a sulfur-containing compound and a lithium-containing compound, wherein the reaction product contains Li element, S element and O element.

[0009] In some embodiments, the weight content of S element in the electrode active material is 500-5000 ppm, for example, 500-1000 ppm, 1000-1500 ppm, 1500-2000 ppm, 2000-2500 ppm, 2500-3000 ppm, 3000-3500 ppm, 3500-4000 ppm, 4000-4500 ppm or 4500-5000 ppm, for example, 540-4360 ppm.

[0010] In some embodiments, the coating layer further contains one or more of the elements B, P and F;

[0011] If element B is contained, the weight content of element B in the electrode active material is 500-3000 ppm (e.g., 860-910 ppm);

[0012] If P element is contained, the weight content of P element in the electrode active material is 200-1500 ppm (e.g. 690-870 ppm);

[0013] If the F element is contained, the weight content of the F element in the electrode active material is 500-3000 ppm (eg, 1070-2100 ppm).

[0014] In some embodiments, the lithium-containing compound comprises a lithium salt;

[0015] Optionally, the lithium-containing compound includes one or more of the following: Li2O, LiOH and Li2CO3, LiNO3, LiPF6, lithium oxalate, lithium acetate, LiClO4, LiBF4, LiCF3SO3, LiAsF6, LiAlCl4, LiN(CF3SO2)2 and LiC(SO2CF3)3.

[0016] In some embodiments, the sulfur-containing compound is an organic sulfur-containing compound.

[0017] In some embodiments, the sulfur-containing compound includes one or more of the following: thiols, thiophenols, thioethers, thioaldehydes, thioketones, thiocarboxylic acids, sulfoxides, sulfones, sulfur oxyacids, and derivatives thereof.

[0018] In some embodiments, the sulfur-containing compound includes one or more of the following: thioethers (eg, linear thioethers or cyclic thioethers), sulfoxides, sulfones, sulfur oxyacids (eg, sulfonic acid, sulfinic acid, or sulfenic acid), and derivatives thereof.

[0019] In some embodiments, the sulfur-containing compound includes one or more of the following: sulfoxides, sulfones, sulfur oxyacids (eg, sulfonic acid, sulfinic acid, or sulfenic acid), and derivatives thereof.

[0020] In some embodiments, the derivative of the sulfur-containing acid includes one or more of the following: an ester of the sulfur-containing acid, a salt of the sulfur-containing acid (e.g., a lithium salt of the sulfur-containing acid), an acyl halide of the sulfur-containing acid, an amide of the sulfur-containing acid, and an amide lithium salt of the sulfur-containing acid.

[0021] In some embodiments, the sulfur oxyacid refers to an organic sulfur oxyacid.

[0022] In some embodiments, the sulfur oxyacid is a sulfonic acid, a sulfinic acid, or a sulfenic acid.

[0023] In some embodiments, the derivative of the sulfur-containing acid includes one or more of the following: an ester of the sulfur-containing acid, a salt of the sulfur-containing acid (e.g., a lithium salt of the sulfur-containing acid), an acyl halide of the sulfur-containing acid, an amide of the sulfur-containing acid, and an amide lithium salt of the sulfur-containing acid.

[0024] In some embodiments, the sulfur-containing compound includes one or more of the following:

[0025] R1-S(=O)2-R2, R1-C(=S)-R2, R1-CSC-R2 or R1-S(=O)2-LiN-S(=O)2-R2, wherein R1 and R2 are each independently selected from hydroxyl, amino, C 1-6 An alkyl group, an aryl group, a halogen atom (such as F, Cl, Br or I) and a hydrogen atom.

[0026] In some embodiments, the sulfur-containing compound comprises R1-S(=O)2-R2, wherein R1 is hydroxyl, and R2 is selected from amino, C 1-6 an alkyl group and a halogen atom (eg, F, Cl, Br or I).

[0027] In some embodiments, the sulfur-containing compound comprises R1-C(=S)-R2, wherein R1 is amino and R2 is C 1-6 alkyl.

[0028] In some embodiments, the sulfur-containing compound comprises Wherein, R1 and R2 are each independently a hydrogen atom or a C 1-6 alkyl.

[0029] In some embodiments, the sulfur-containing compound comprises R1-CSC-R2, wherein R1 and R2 are each independently a hydrogen atom or a C 1-6 alkyl.

[0030] In some embodiments, the sulfur-containing compound includes R1-S(=O)2-LiN-S(=O)2-R2, wherein R1 and R2 are each independently a halogen atom.

[0031] In some embodiments, the sulfur-containing compound includes one or more of the following: sulfamide, aminomethanesulfonic acid, lithium bis(fluorosulfonyl)imide, thiopropionamide, thioisobutyramide, propylene sulfide, and methyl ethyl sulfide.

[0032] In some embodiments, the sulfur-containing compound includes one or more of the following: sulfamide, aminomethanesulfonic acid, lithium bis(fluorosulfonyl)imide, thiopropionamide, thioisobutyramide, propylene sulfide, and methyl ethyl sulfide.

[0033] In some embodiments, the sulfur-containing compound includes one or more of the following:

[0034]

[0035] In some embodiments, C 1-6 The alkyl group is substituted with an amino group. For example, C 1-6 The alkyl group is aminomethyl.

[0036] In some embodiments, C 1-6 The alkyl group is selected from the group consisting of methyl, ethyl, propyl, butyl, pentyl, and hexyl.

[0037] In some embodiments, the lithium-containing compound and the sulfur-containing compound are two different compounds.

[0038] In some embodiments, the reaction product of the sulfur-containing compound and the lithium-containing compound is a Li—SO compound.

[0039] In some embodiments, the reaction product of the sulfur-containing compound and the lithium-containing compound includes one or more of the following: a sulfur-containing compound substituted with lithium, lithium sulfate, lithium sulfite.

[0040] In some embodiments, the ternary material includes one or more of: lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide;

[0041] Optionally, the chemical formula of lithium nickel cobalt manganese oxide is Li x Ni a Co b Mn c M 1 (1-a-b-c) O2, 0.5≤x≤1.2, 0.3≤a≤1, 0≤b≤0.5, 0≤c≤0.6, M 1 A combination of one or more selected from Zr, Zn, Ti, Sr, Sb, Y, W, Al, B, P, and F.

[0042] In some embodiments, x = 0.5-0.6, 0.6-0.7, 0.7-0.8, 0.8-0.9, 0.9-1, 1-1.1, or 1.1-1.2.

[0043] In some embodiments, a=0.3-0.4, 0.4-0.5, 0.5-0.6, 0.6-0.7, 0.7-0.8, 0.8-0.9, or 0.9-1.

[0044] In some embodiments, b = 0-0.1, 0.1-0.2, 0.2-0.3, 0.3-0.4, or 0.4-0.5.

[0045] In some embodiments, c = 0-0.1, 0.1-0.2, 0.2-0.3, 0.3-0.4, 0.4-0.5, or 0.5-0.6.

[0046] Optionally, the chemical formula of lithium nickel cobalt aluminum oxide is Li x Ni d Co e Al f M 2 (1-d-e-f) O2, 0.5≤x≤1.2, 0.5≤d≤1, 0≤e≤0.5, 0≤f≤0.5, M 2 A combination of one or more selected from Zr, Mg, Ba, Ti, Sr, Sb, Y, W, and B.

[0047] In some embodiments, x = 0.5-0.6, 0.6-0.7, 0.7-0.8, 0.8-0.9, 0.9-1, 1-1.1, or 1.1-1.2.

[0048] In some embodiments, d=0.5-0.6, 0.6-0.7, 0.7-0.8, 0.8-0.9, or 0.9-1.

[0049] In some embodiments, e = 0-0.1, 0.1-0.2, 0.2-0.3, 0.3-0.4, or 0.4-0.5.

[0050] In some embodiments, f = 0-0.1, 0.1-0.2, 0.2-0.3, 0.3-0.4, 0.4-0.5.

[0051] In some embodiments, the electrode active material comprises:

[0052] core, the core contains ternary materials;

[0053] A first coating layer, the first coating layer covers at least a portion of the surface of the core, the first coating layer contains Al element, for example, the first coating layer contains aluminum oxide, aluminum fluoride, aluminum phosphate;

[0054] A second coating layer, the second coating layer covers at least a portion of the surface of the core, the second coating layer contains a reaction product of a sulfur-containing compound and a lithium-containing compound, and the reaction product contains Li element, S element and O element;

[0055] The first coating layer and the second coating layer have different compositions.

[0056] Unless otherwise specified, the coating layer mentioned in the present disclosure is a coating layer containing a reaction product of a sulfur-containing compound and a lithium-containing compound.

[0057] In some embodiments, the particle size (e.g., D V 50 particle size) is 1 to 25 μm, for example 1 to 10 μm.

[0058] In some aspects, the present disclosure provides a method for preparing an electrode active material having a coating layer, comprising:

[0059] a) providing a core material and a coating layer forming material, wherein the core material contains a ternary material and the coating layer forming material contains a sulfur-containing compound;

[0060] Wherein, step a) has one or more of the following features a1) to a2):

[0061] a1) There are lithium-containing compounds on the surface of the nuclear material;

[0062] a2) the coating layer forming material further contains a lithium-containing compound;

[0063] b) treating the core material with a coating layer forming material so that a reaction product of a sulfur-containing compound and a lithium-containing compound is formed on the surface of the core material, wherein the reaction product contains Li element, S element and O element.

[0064] In some embodiments, in item a1), the lithium-containing compound is a basic lithium-containing compound.

[0065] In some embodiments, in item a2), the lithium-containing compound is a neutral lithium-containing compound or an acidic lithium-containing compound.

[0066] In some embodiments, the coating layer forming material further contains one or more of the B element, the P element, and the F element;

[0067] If the B element is contained, the molar ratio of the B element to the S element in the coating layer forming material is 2-5:4-7 (e.g., 2-5:5-7);

[0068] If the P element is contained, the molar ratio of the P element to the S element in the coating layer forming material is 1 to 3:4 to 6 (e.g., 2:5);

[0069] If the F element is contained, the molar ratio of the F element to the S element in the coating layer forming material is 10 to 15:4 to 6 (eg, 12:5).

[0070] In some embodiments, the operation of treating the core material with the coating-forming material comprises: applying a solution containing the coating-forming material to the surface of the core material, followed by heat treatment;

[0071] Optionally, the temperature of the heat treatment is 80 to 300°C;

[0072] Optionally, the heat treatment time is 3 to 20 hours.

[0073] In some embodiments, the operation of applying a solution containing a coating-forming material to the surface of the core material includes: dispersing the core material into the solution containing the coating-forming material, and then separating the core material from the solution.

[0074] In some embodiments, the content of the sulfur-containing compound in the solution containing the coating layer forming material is 0.1 to 5 mol / L (eg, 0.2 to 2 mol / L).

[0075] In some embodiments, the content of the lithium-containing compound in the solution containing the coating layer forming material is 0.1 to 3 mol / L (eg, 0.3 to 0.5 mol / L).

[0076] In some embodiments, the solvent in the solution containing the coating layer forming material includes one or more of the following substances: water, ethanol, NMP. Optionally, the solvent is alcohol with a concentration of 90-95 vol%.

[0077] In some embodiments, the lithium-containing compound is defined as any one of the above.

[0078] In some embodiments, the sulfur-containing compound is defined as any one of the above.

[0079] In some embodiments, the ternary material is defined as any one of the above.

[0080] In some aspects, an electrode active material having a coating layer is provided, which is prepared by any of the above methods.

[0081] In some aspects, an electrode is provided, comprising any of the electrode active materials described above.

[0082] In some aspects, a battery is provided, comprising any of the electrode active materials described above.

[0083] In some aspects, a device is provided, comprising any of the above-mentioned batteries, wherein the battery serves as an energy storage unit of the device.

[0084] In some embodiments, the device is an electrically powered device and the battery is used to power the electrically powered device.

[0085] In some embodiments, the method for preparing the electrode active material with the coating layer is a wet method.

[0086] In some aspects, a device is provided, comprising the above-mentioned battery, wherein the battery serves as an energy storage unit of the device.

[0087] In some embodiments, the electrolyte of the battery can be selected according to demand. The electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). When the electrolyte is an electrolyte, the electrolyte includes an electrolyte salt and a solvent. The electrolyte salt can be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalate phosphate)) and LiTFOP (lithium tetrafluorooxalate phosphate). The solvent may be one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0088] In some embodiments, the battery further comprises a separator, which serves as a separator between the positive electrode and the negative electrode.

[0089] In some embodiments, the isolation membrane can be any known porous structure isolation membrane with good chemical stability and mechanical stability, such as one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different.

[0090] In some embodiments, the device is an electrically powered device and the battery provides power to the electrically powered device.

[0091] In some embodiments, the electric device may be an electrical appliance, such as a household appliance, a commercial appliance, an industrial appliance, or the like.

[0092] In some embodiments, the electric device may be an electric vehicle, such as an electric car. The electric vehicle may be either a pure electric vehicle or a hybrid vehicle.

[0093] In some embodiments, "comprising", "including" or "containing" may mean that the weight content is greater than zero, such as 1% or more, such as 10% or more, such as 20% or more, such as 30% or more, such as 40% or more, such as 50% or more, such as 60% or more, such as 70% or more, such as 80% or more, such as 90% or more, such as 100%. When the content is 100%, the meaning of "comprising", "including" or "containing" is equivalent to "consisting of...".

[0094] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0095] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number, and "several" in "one or several" means two or more.

[0096] The above summary of the invention is not intended to describe each disclosed embodiment or each implementation in the application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided through a series of embodiments, which can be used in various combinations. In each example, the enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0097] Terminology explanation:

[0098] If the present invention uses the following terms, they can be understood in the following non-limiting manner:

[0099] "Electrode active material" refers to a battery material having a specific composition and crystal structure that enables it to intercalate and deintercalate lithium ions.

[0100] "Electrode" refers to the component containing electrode active materials that participates in the electrochemical reaction of the battery.

[0101] "Battery" refers to a single physical module that includes one or more battery cells to provide higher voltage and capacity. "Battery cell" refers to a battery cell that can be charged and discharged independently. The battery cell structure includes a positive electrode, a negative electrode, a separator, an electrolyte, and an outer packaging for encapsulating the positive electrode plate, the negative electrode plate, the separator and the electrolyte. This application has no special restrictions on the type and shape of the battery cell, which can be a soft-pack battery cell, a cylindrical battery cell, a square battery cell, and other types of battery cells.

[0102] Batteries may include battery cells, battery modules and battery packs. Battery modules are formed by electrically connecting a certain number of battery cells together and placing them in a frame in order to protect the battery cells from external impact, heat, vibration, etc. The battery pack is the final state of the battery system installed in electric vehicles and other electrical devices. Most of the current battery packs are made by assembling various control and protection systems such as battery management systems and thermal management components on one or more battery modules. With the development of technology, the battery module level can be omitted, that is, the battery pack is directly formed from the battery cells. This improvement has increased the weight energy density and volume energy density of the battery system while significantly reducing the number of components.

[0103] "Single crystal", also called single particle or primary particle, has a microscopic appearance of substantially non-agglomerated, dispersed particles. Single crystals may be irregularly shaped particles.

[0104] "Polycrystalline" refers to a secondary particle formed by the aggregation of two or more primary particles. Polycrystalline can be spherical particles.

[0105] The terms "powder", "particles" are used interchangeably herein. These terms also arbitrarily have the following characteristics: hollow, dense, porous, semi-porous, coated, uncoated, multilayer, laminated, simple, complex, dendritic, inorganic, organic, elemental, non-elemental, composite, doped, undoped, spherical, non-spherical, surface functionalized, surface non-functionalized, stoichiometric and non-stoichiometric forms or substances. In addition, the term powder in its general sense includes one-dimensional materials (fibers, tubes, etc.), two-dimensional materials (pieces, films, laminates, planes, etc.) and three-dimensional materials (spheres, cones, ovoids, cylinders, cubes, monoclinic, dumbbells, hexagons, truncated dodecahedrons, irregular shaped structures, etc.).

[0106] The term "spherical" as used herein refers to a true sphere, an ellipsoid, or a spheroid-like shape.

[0107] The term "D V "10" refers to the 10th percentile volume-based particle size; "D V "50" refers to the 50th percentile volume-based particle size; "D V "90" refers to the 90th percentile volume-based particle size. Particle size is measured using laser diffraction.

[0108] The term "lithium salt" refers to a lithium-containing compound that can dissociate in a solvent to form lithium ions.

[0109] The term "thiol" refers to an alcohol molecule in which the hydroxyl group is replaced by -SH.

[0110] The term "thiophenol" refers to a phenol molecule in which the phenolic hydroxyl group is replaced by -SH.

[0111] The term "thioether" refers to a compound having the structure R3-S-R4, wherein R3 and R4 are each independently an alkyl group.

[0112] The term "thialdehyde" refers to an aldehyde molecule in which the aldehyde group C(O)H is replaced by C(S)H.

[0113] The term "thioketone" refers to a ketone molecule in which the carbonyl group -C(O)- is replaced by -C(S)-.

[0114] The term "thiocarboxylic acid" refers to a carboxylic acid molecule in which the -COOH group is replaced by CO-SH, CS-OH or CSSH.

[0115] The term "sulfone" refers to a compound having the group -S(O)2R, where R is alkyl, aryl, or heteroaryl.

[0116] The term "sulfoxide" refers to a compound having the group -S(O)R, where R is alkyl, aryl, or heteroaryl.

[0117] The terms "sulfonic acid", "sulfinic acid" and "sulfenic acid" refer to compounds having -S(O)2OH, -S(O)OH and -SOH, respectively.

[0118] The term "amino" refers to unsubstituted or substituted amino groups, substituted amino groups are for example alkyl substituted amino groups, for example methylamino groups.

[0119] The term "C 1-6 "Alkyl" refers to an alkyl group having 1 to 6 carbon atoms, which may be branched or straight-chain, saturated or unsaturated, unsubstituted or mono- or poly-substituted

[0120] Beneficial Effects

[0121] The present disclosure provides an electrode active material with a coating layer, comprising a core and a coating layer, wherein the core contains a ternary material; the coating layer coats the core, and the coating layer contains a reaction product of a sulfur-containing compound and a lithium-containing compound, wherein the reaction product contains Li element, S element and O element.

[0122] One or more technical solutions disclosed in this disclosure have one or more of the following beneficial effects:

[0123] 1) The electrode active material or composition is used in a battery, showing an improved specific capacity;

[0124] 2) The electrode active material or composition is used in a battery and exhibits improved cycle performance;

[0125] 3) The electrode active material or composition is used in a battery, showing a reduced DC internal resistance growth rate during the cycle;

[0126] 4) The electrode active material or composition is used in a battery and exhibits lower gas generation;

[0127] 5) The electrode active material or composition is used in a battery, and the battery exhibits better performance at a higher voltage;

[0128] 6) The electrode active material or composition can be prepared into slurry under higher humidity and still have good processing performance and / or electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0129] Figure 1 The scanning electron microscope images of lithium nickel cobalt manganese oxide No. 10, (a)-(d) show images at different magnifications or positions.

[0130] Figure 2 These are scanning electron microscope images of lithium nickel cobalt manganese oxide No. 24, and (a) to (d) show images at different magnifications or positions.

[0131] Figure 3 A schematic diagram of a battery according to one embodiment of the present application is shown.

[0132] Figure 4 (A) shows a schematic diagram of a battery housing, Figure 4 (B) shows a schematic diagram of the battery housing and cover plate.

[0133] Figure 5 (A) and (B) respectively show a side view and a bottom view of a car according to one embodiment of the present application. Specific embodiments

[0134] The electrode active material with a coating layer and the preparation method thereof disclosed in the present invention are described in detail below through examples. A battery is assembled using the electrode active material, and one or more of the following properties are tested: capacity retention rate, DC impedance, gas production, and slurry processing performance.

[0135] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0136] 1. Electrode active material powder (core material)

[0137] serial number Chemical formula Morphological characteristics <![CDATA[D V 10]]> <![CDATA[D V 50]]> <![CDATA[D V 90]]> Residual lithium content* NCM1 <![CDATA[LiNi 0.82 What 0.118 Mn 0.058 Zr 0.004 O2]]> Single Crystal 1.8 3.6 7.2 0.21% NCM2 <![CDATA[LiNi 0.644 What 0.098 Mn 0.252 Those 0.006 O2]]> Single Crystal 1.54 3.23 6.6 0.08% NCM3 <![CDATA[LiNi 0.548 What 0.05 Mn 0.40 Wed 0.002 O2]]> Single Crystal 1.81 3.76 7.44 0.06% NCM4 <![CDATA[LiNi 0.818 What 0.119 Mn 0.059 Zr 0.002 Wed 0.002 O2]]> polycrystalline 5.39 10 17.4 0.26% NCA <![CDATA[LiNi 0.83 Co 0.10 Al 0.065 Ba 0.005 O2]]> polycrystalline 5.21 9.53 16.2 0.31%

[0138] *The detection method of residual lithium content is as follows:

[0139] Reference standard: GB / T 9725-2007 General rules for potentiometric titration of chemical reagents

[0140] Equipment parameters: 905Ttrando potentiometric titrator; Electrode: composite pH electrode; Reagent: 0.5mol / L HCl solution; Environmental parameters: 15~28℃, ambient humidity ≤80%

[0141] Test method: Weigh 30g sample and mix with 100g deionized water, let it stand and filter, then use 0.5mol / L HCL solution to titrate the filtrate using 905Ttrando potentiometric titrator to measure the CO3 in the filtrate. 2- and OH - The content is calculated according to the stoichiometric ratio of Li2CO3 and LiOH. 1 mol CO3 2- Corresponding to 2 mol Li element, 1 mol OH - Corresponding to 1 mol of Li element, the residual lithium weight content calculated as Li element is obtained after addition.

[0142] 2. Coating method

[0143] Step 1: Provide the above ternary material powder as the core material.

[0144] Step 2: Provide a solution containing a coating layer forming material. The formula of the solution containing the coating layer forming material is shown in Table 1.

[0145] Step 3: Mix the products of step 1 and step 2 in a weight ratio of 1:1, stir for 30 minutes after mixing, separate the solid and liquid, and collect the solid;

[0146] Step 4: The solid obtained in the previous step is heat-treated in a closed environment with an inert atmosphere. The heat treatment conditions are shown in Table 1 to obtain an electrode active material with a coating layer.

[0147] In the above embodiments, alkaline lithium-containing compounds (such as Li2O, LiOH and Li2CO3, etc.) exist on the surface of the core material. The alkaline lithium-containing compounds react with the sulfur-containing compounds during the coating process to generate reaction products of the sulfur-containing compounds and the lithium-containing compounds. The reaction products contain Li element, S element and O element.

[0148] After the core material is coated according to the above method, an electrode active material with a coating layer is obtained. Specific process parameters are shown in Table 1.

[0149]

[0150]

[0151] Material physical and electrical properties testing

[0152] Table 1 shows 24 samples, including electrode active materials that have been coated and electrode active materials that have not been coated. The above 24 samples are tested by the following test methods:

[0153] 1. Preparation of batteries

[0154] Preparation of positive electrode sheets: Under an ambient humidity of 2%, the electrode active material prepared in the above embodiment / comparative example is mixed with conductive carbon black and binder PVDF in a mass ratio of 96:2.5:1.5, and solvent N-methylpyrrolidone (NMP) is added, the mass of the solvent accounts for 30% of the total weight of the slurry, and stirred to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, and cold pressed using a roller press to obtain a positive electrode sheet, and the compacted density of the obtained positive electrode sheet is 3.5g / cc to 4.0g / cc.

[0155] Preparation of negative electrode sheets: artificial graphite is used as the negative electrode active material. In the negative electrode slurry, the solid components are artificial graphite, styrene butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), and conductive carbon black in a ratio of 96:2:1:1. The slurry solvent component is water, and the solvent accounts for 50% of the slurry weight. The negative electrode slurry is evenly coated on both sides of the negative electrode collector copper foil, and cold pressed using a roller press to obtain a negative electrode sheet. The compaction density of the obtained negative electrode sheet is 1.65g / cc.

[0156] Isolation membrane: PP / PE composite membrane is used.

[0157] Electrolyte: 1 mol / L LiPF6 solution, the solvent of which mainly includes ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC).

[0158] Battery assembly: overlap the above-mentioned negative electrode sheet, separator, and positive electrode sheet and then wind them to obtain a roll core, weld the pole ears on the copper-aluminum foil current collector where the positive and negative electrode sheets are exposed from the roll core, and package them in an aluminum-plastic composite material packaging bag with a thickness of 153μm. After injecting electrolyte, seal the bag and form it at 45°C. After the formation is completed, extract the gas generated by the formation and cut off the excess packaging bag to obtain a battery with a height of 130mm, a thickness of 4mm, and a width of 60mm.

[0159] 2. First-week discharge capacity and test method

[0160] Use a Xinwei charger / discharger (5V / 6A) and a constant test room temperature (25°C) to charge and discharge the battery. The charging and discharging method is as follows:

[0161] 1. Keep the temperature constant at 25°C and let it stand for 10 minutes;

[0162] 2. Charge at a constant current rate of 0.33C to the charging cut-off voltage (the charging cut-off voltage setting of the battery cell corresponding to each active material is shown in the following table), and then charge at a constant voltage rate of the charging cut-off voltage until the charging current is ≤0.05C;

[0163] Electrode active materials Corresponding to the charging cut-off voltage of the battery cell NCM1, NCM4, NCA 4.2V NCM2, NCM3 4.35V

[0164] 3. Let stand for 5 minutes;

[0165] 4. Discharge at a constant current rate of 0.33C to a discharge cut-off voltage (2.8V in the following embodiments, which can be adjusted according to the different batteries to be tested);

[0166] The first-week discharge specific capacity is measured as the test result.

[0167] Among them, the charge / discharge current is the preset rate multiplied by the rated capacity of the battery cell, and the rated capacity is based on the battery capacity recognized in the GBT certification document of the battery cell, the battery module to which the battery cell belongs, or the battery pack to which the battery cell belongs.

[0168] 3. Capacity retention rate test method

[0169] Use Tenda 220L high and low temperature box for testing. The charging and discharging methods are as follows:

[0170] 1. Adjust the furnace temperature to the preset temperature and let it stand for 2 hours.

[0171] 2. Charge at a constant current rate of 1C to the charging cut-off voltage (the charging cut-off voltage settings of each material are shown above), and then charge at a constant voltage at the charging cut-off voltage until the charging current is ≤0.05C;

[0172] 3. Let stand for 5 minutes;

[0173] 4. Discharge at a constant current rate of 1C to a discharge cut-off voltage (the discharge cut-off voltage used in the following embodiments is specifically 2.8V);

[0174] 5. Let stand for 5 minutes;

[0175] 6. Repeat steps 2 to 5.

[0176] 4. Gas production test method:

[0177] After the battery cells are fully charged, they are stored in a 70°C high-temperature furnace. At regular intervals, the volume of the battery cells is measured using the water displacement method. The volume changes before and after storage are compared to obtain the gas production volume change rate.

[0178] 5. Method for extracting DCR growth rate during the cycle:

[0179] During the cycle, the average voltage / average current of each cycle before charging to 100% SOC is extracted to obtain the DCR of the cycle number. After extraction according to the cycle number, the DCR growth rate during the cycle is obtained.

[0180] 6. Particle size distribution test method:

[0181] The laser particle size test was performed using a Mastersizer 3000E laser particle size analyzer from Malvern Instruments Ltd., UK. The detection method can refer to GB / T 19077-2016 particle size distribution laser diffraction method. The test was performed by dispersing the electrode active material in water, and the particle refractive index was 1.69.

[0182] The method for testing the particle size of the electrode active material in the finished electrode is as follows: scrape the positive electrode plate to remove the powder, collect the scraped powder and place it in a sintering furnace, sinter at 600°C for 4 hours to remove the conductive carbon and binder in the powder to obtain the electrode active material. The laser particle size test of the electrode active material is performed using a Mastersizer 3000E laser particle size analyzer.

[0183] 7. Test methods for sulfur, boron and phosphorus content:

[0184] Test method: Inductively coupled plasma atomic emission spectrometry

[0185] Instrument model: ICP-OES, Thermo ICAP7400

[0186] Sample weight: 0.4g

[0187] Digestion method: flat plate digestion

[0188] Type and volume of acid used for digestion: 10 ml aqua regia (concentrated nitric acid:concentrated hydrochloric acid (volume ratio) = 1:1)

[0189] Fixed volume: 100mL

[0190] Quantitative method: Standard curve method

[0191] 8. Method for determining fluorine content:

[0192] Instrument model: ICS-900 ion chromatography tester

[0193] Reference standard: General rules for ion chromatography analysis JY / T202-1996

[0194] Determination method: Take 0.4 g of electrode active material and completely digest it in 10 mL of aqua regia (concentrated nitric acid:concentrated hydrochloric acid (volume ratio) = 1:1), dilute the resulting solution to 250 mL, and then inject it for testing.

[0195] Detailed description of the test results of electrode active materials

[0196] The test results of samples No. 1 to No. 24 obtained by testing the above method are described in detail below.

[0197] 1. Microscopic morphology and particle size

[0198] (1) Microscopic morphology

[0199] Figure 1 The scanning electron microscope photographs of the electrode active material No. 10, wherein (a) to (d) show photographs with scales of 10 μm, 2 μm, 1 μm and 1 μm, respectively. The particles of the electrode active material have irregular particle shapes and a single crystal microstructure.

[0200] Figure 2 The scanning electron microscope photographs of the electrode active material No. 24, (a)-(d) show photographs at different magnifications or positions. Among them, (a) to (d) show photographs with scales of 10 μm, 2 μm, 10 μm and 1 μm respectively. The particles of the electrode active material have a spherical particle shape and a polycrystalline microstructure.

[0201] (2) Particle size distribution

[0202] The particle size distribution of the electrode active materials No. 1, 2, 3, 14, 21 is as follows:

[0203] Table 3

[0204]

[0205] (3) Element content test

[0206] In the electrode active materials No. 1-24, the contents of S, B, P, and F are as follows:

[0207] Table 4

[0208]

[0209]

[0210] The electrode active materials No. 11 to 13, 18, and 24 have not been coated. Since the raw material precursor contains sulfur, the above electrode active materials inevitably contain a small amount of sulfur residue (<400 ppm).

[0211] (4) The electrode active materials No. 1 to 24 were assembled into lithium ion secondary batteries according to the above method, and the performance of the batteries was tested. The results are as follows:

[0212] Table 5

[0213]

[0214]

[0215] * Capacity retention and DC impedance are tested at a preset ambient temperature of 45°C

[0216] (5) Slurry processing performance:

[0217] Under the relative humidity environment of 2% and 45%, the electrode active material No. 23 was configured into a slurry, and the formula was as follows: the electrode active material, conductive carbon black, and binder PVDF were mixed in a mass ratio of 96:2.5:1.5, and a solvent N-methylpyrrolidone (NMP) was added, and the mass of the solvent accounted for 30% of the total weight of the slurry, and stirred to form a uniform positive electrode slurry. The slurries prepared under the two different humidity environments were allowed to stand, and the viscosity of the electrode slurry was analyzed using a rheometer (Gemini 150Rheometer, Malvern Instruments ltd) at regular intervals.

[0218] At the same time, according to the above test method, sample No. 24 was also treated in the same way as a reference group. The results are shown in the following table:

[0219] Table 6

[0220]

[0221] ∞ means the viscosity is too high to be measured accurately.

[0222] Under the relative humidity environment of 2% and 45%, the electrode active material No. 17 was configured into a slurry, and the formula was as follows: the electrode active material, conductive carbon black, and binder PVDF were mixed in a mass ratio of 96:2.5:1.5, and a solvent N-methylpyrrolidone (NMP) was added, and the mass of the solvent accounted for 30% of the total weight of the slurry, and stirred to form a uniform positive electrode slurry. The slurries prepared under the two different humidity environments were allowed to stand, and the viscosity of the electrode slurry was analyzed using a rheometer (Gemini 150Rheometer, Malvern Instruments ltd) at regular intervals.

[0223] At the same time, according to the above test method, the sample No. 18 was also treated in the same way as the reference group. The results are shown in the following table:

[0224] Table 7

[0225]

[0226] ∞ means the viscosity is too high to be measured accurately.

[0227] It can be seen from the above experimental data that compared with the electrode active materials without coating layers (No. 18, 24), the electrode active materials with coating layers (No. 17, 23) have improved processing performance. Specifically, whether the electrode active materials with coating layers (No. 17, 23) are prepared at a relative humidity of 2% or 45%, the slurry has a relatively low viscosity, and there is no obvious gel phenomenon when observed by naked eye. Such a slurry is beneficial for subsequent coating and cold pressing processes, and is beneficial for improving the electrical performance of the battery.

[0228] From the above experimental data, it can be seen that the coating layer containing the reaction product of the lithium-containing compound and the sulfur-containing compound can improve the performance of the electrode active material. Compared with the electrode active materials without the coating layer (No. 11-13, 18, 24), the electrode active materials with the coating layer (No. 1-10, 14-17, 19-23) have the following beneficial effects:

[0229] 1) Improved specific capacity;

[0230] 2) Improved cycle performance;

[0231] 3) Reduced DC internal resistance;

[0232] 4) Lower gas production;

[0233] 5) Show better performance at higher voltage.

[0234] 6) Able to stably produce and process under high relative humidity.

[0235] According to some embodiments of the present application, the present application provides a battery. Figure 3 A battery 10 according to one embodiment of the present application is shown. Figure 4 (A) shows a schematic diagram of a battery housing, Figure 4 (B) shows a schematic diagram of the battery housing and cover. Figures 3-4As shown, in this embodiment, it can also be referred to as a battery cell 20, which includes a box 21, an electrode assembly 22 and an electrolyte, wherein the electrode assembly 22 is contained in the box 21 of the battery cell 20, and the electrode assembly 22 includes a positive electrode sheet, a negative electrode sheet and a separator. The separator can be a separator prepared in the embodiment of the present application. The electrode assembly 22 can be a winding structure or a laminated structure, for example, it can be a structure actually adopted in the embodiment of the present application. The box 21 includes a shell 211 and a cover plate 212. The shell 211 includes a housing 211a formed by a plurality of walls and an opening 211b. The cover plate 212 is arranged at the opening 211b to close the housing chamber 211a. In addition to the electrode assembly 22, the housing chamber 211a also contains an electrolyte. The positive electrode sheet and the negative electrode sheet in the electrode assembly 22 are generally provided with tabs, and the tabs generally include positive tabs and negative tabs. According to some embodiments of the present application, the number of positive electrode tabs is multiple and stacked together, and the number of negative electrode tabs is multiple and stacked together. The tabs are connected to the positive electrode terminal 214a and the negative electrode terminal 214b outside the battery cell 20 through the connecting member 23. In the description of the present application, the positive electrode terminal 214a and the negative electrode terminal 214b are also collectively referred to as the electrode terminal 214. For a square battery cell, the electrode terminal 214 can generally be set on the cover plate 212.

[0236] According to some embodiments of the present application, the present application provides a device, which may include mobile phones, portable devices, laptop computers, electric vehicles, electric cars, ships, spacecraft, electric toys and electric tools, etc., wherein the spacecraft may include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., power tools include metal cutting power tools, grinding power tools, assembly power tools and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.

[0237] In this embodiment, the device includes a car. For example, Figure 5 (A) and (B) respectively show a side view and a bottom view of a car according to an embodiment of the present application. The car can be a fuel car, a gas car or a new energy car, and the new energy car can be a pure electric car, a hybrid car or an extended range car, etc. Figure 5 As shown in (A), a battery 10 may be provided inside the automobile 1. Figure 5(A) shows that the battery 10 is arranged at the bottom of the vehicle, but it is also possible to consider arranging the battery 10 at the front or rear of the vehicle 1 as needed. During the operation of the vehicle, the battery 10 can provide power to the vehicle 1 in an intermittent or continuous manner. For example, the battery 10 can be used to supply power to the lights, LCD screen, and lighter of the vehicle 1. In the case of a hybrid vehicle or an electric vehicle, the battery 10 can also be used to supply driving power to the vehicle 1. Figure 5 As shown in (B), the automobile 1 may also include a controller 30 and a motor 40. The controller 30 is used to control the battery 10 to supply power to the motor 40, for example, for starting, navigating, and driving the automobile 1. In another embodiment of the present application, the battery 10 may not only be used as an operating power source for the automobile 1, but may also be used as a driving power source for the automobile 1, replacing or partially replacing fuel or natural gas to provide driving power for the automobile 1. According to one embodiment of the present application, the battery 10 used in the automobile may also include multiple Figures 3-4 A battery pack of battery cells 20 is shown.

[0238] The above is only a specific implementation method, but the protection scope is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in this application, and these modifications or replacements should be included in the protection scope. Therefore, the protection scope should be based on the protection scope of the claims.

Claims

1. A method for preparing an electrode active material having a coating layer, wherein: include: a) providing a core material and a coating layer forming material, wherein the core material contains a ternary material and the coating layer forming material contains a sulfur-containing compound; Wherein, step a) has one or more of the following features a1) to a2): a1) the surface of the core material has a lithium-containing compound; a2) the coating layer forming material further contains a lithium-containing compound; b) treating the core material with a coating layer forming material so that a reaction product of a sulfur-containing compound and a lithium-containing compound is formed on the surface of the core material, wherein the reaction product contains Li element, S element and O element, The sulfur-containing compound includes one or more of the following: mercaptans, thiophenols, thioethers, thioaldehydes, thioketones, thiocarboxylic acids, sulfoxides, sulfones, sulfur-containing oxyacids and their derivatives; The operation of treating the core material with the coating layer forming material includes: applying a solution containing the coating layer forming material to the surface of the core material, and then performing a heat treatment.

2. The preparation method according to claim 1, wherein In item a1), the lithium-containing compound is an alkaline lithium-containing compound.

3. The preparation method according to claim 1, wherein In item a2), the lithium-containing compound is a neutral lithium-containing compound or an acidic lithium-containing compound.

4. The preparation method according to any one of claims 1 to 3, wherein The coating layer forming material further contains one or more of the elements B, P and F; Under the condition of containing B element, in the coating layer forming material, the molar ratio of B element to S element is 2-5:4-7; Under the condition of containing P element, in the coating layer forming material, the molar ratio of P element to S element is 1-3:4-6; Under the condition of containing F element, in the coating layer forming material, the molar ratio of F element to S element is 10-15:4-6.

5. The preparation method according to any one of claims 1 to 3, wherein The temperature of the heat treatment is 80-300°C.

6. The preparation method according to any one of claims 1 to 3, wherein The heat treatment time is 3 to 20 hours.

7. The preparation method according to any one of claims 1 to 3, wherein It has one or more of the following characteristics: - the content of the sulfur-containing compound in the solution containing the coating layer forming material is 0.1 to 5 mol / L; - the content of the lithium compound in the solution containing the coating layer forming material is 0.1 to 3 mol / L; - In the solution containing the coating layer forming material, the solvent includes one or more of the following substances: water, ethanol, and NMP.

8. The preparation method according to any one of claims 1 to 3, wherein It has one or more of the following characteristics: - the content of the sulfur-containing compound in the solution containing the coating layer forming material is 0.2 to 2 mol / L; - the content of the lithium compound in the solution containing the coating layer forming material is 0.3 to 0.5 mol / L; - In the solution containing the coating layer forming material, the solvent is alcohol with a concentration of 90 to 95 vol%.

9. The preparation method according to claim 1, wherein It has one or more of the following characteristics: - the lithium-containing compound comprises a lithium salt; The ternary material includes one or more of the following: lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

10. The preparation method according to claim 9, wherein: The lithium-containing compound includes one or more of the following: Li2O, LiOH and Li2CO3, LiNO3, LiPF6, lithium oxalate, lithium acetate, LiClO4, LiBF4, LiCF3SO3, LiAsF6, LiAlCl4, LiN(CF3SO2)2 and LiC(SO2CF3)3.

11. The preparation method according to claim 9, wherein: The sulfur-containing oxyacid is a sulfonic acid, a sulfinic acid or a sulfenic acid.

12. The preparation method according to claim 9, wherein: The derivative of the sulfur-containing oxyacid includes one or more of the following: ester of the sulfur-containing oxyacid, salt of the sulfur-containing oxyacid, acyl halide of the sulfur-containing oxyacid, amide of the sulfur-containing oxyacid, and amide lithium salt of the sulfur-containing oxyacid.

13. The preparation method according to claim 12, wherein: The salt of sulfur-containing oxyacid is a lithium salt of sulfur-containing oxyacid.

14. The preparation method according to claim 1, wherein: The sulfur-containing compounds include one or more of the following: R1-S(=O)2-R2, R1-C(=S)-R2, R1-CSC-R2 or R1-S(=O)2- LiN-S(=O)2-R2, wherein R1 and R2 are each independently selected from hydroxyl, amino, C 1-6 Alkyl groups, aryl groups, halogen atoms and hydrogen atoms.

15. The preparation method according to claim 14, wherein: The sulfur-containing compound includes R1-S(=O)2-R2, wherein R1 is a hydroxyl group, and R2 is selected from amino, C 1-6 Alkyl groups and halogen atoms.

16. The preparation method according to claim 14, wherein: The sulfur-containing compound includes R1-C(=S)-R2, wherein R1 is an amino group, R2 is C 1-6 alkyl.

17. The preparation method according to claim 14, wherein: The sulfur-containing compounds include Wherein, R1 and R2 are each independently a hydrogen atom or a C 1-6 alkyl.

18. The preparation method according to claim 14, wherein: The sulfur-containing compound includes R1-CSC-R2, wherein R1 and R2 are each independently a hydrogen atom or a C 1-6 alkyl.

19. The preparation method according to claim 14, wherein: The sulfur-containing compound includes R1-S(=O)2-LiN-S(=O)2-R2, wherein R1 and R2 are each independently a halogen atom.

20. The preparation method according to any one of claims 14, 15 and 19, wherein The halogen atom is F, Cl, Br or I.

21. The preparation method according to claim 1, wherein: The sulfur-containing compound includes one or more of the following: sulfamide, aminomethanesulfonic acid, lithium bis(fluorosulfonyl)imide, thiopropionamide, thioisobutyramide, propylene sulfide, and methyl ethyl sulfide.

22. The preparation method according to claim 9, wherein: The chemical formula of the lithium nickel cobalt manganese oxide is Li x Ni a Co b Mn c M 1 (1-a-b-c) O2, 0.5≤x≤1.2, 0.3≤a≤1, 0≤b≤0.5, 0≤c≤0.6, M 1 A combination of one or more selected from Zr, Zn, Ti, Sr, Sb, Y, W, Al, B, P, and F.

23. The electrode active material according to claim 9, wherein The chemical formula of the lithium nickel cobalt aluminum oxide is Li x Ni d Co e Al f M 2 (1-d-e-f) O2, 0.5≤x≤1.2, 0.5≤d≤1, 0≤e≤0.5, 0≤f≤0.5, M 2 A combination of one or more selected from Zr, Mg, Ba, Ti, Sr, Sb, Y, W, and B.

24. An electrode active material having a coating layer, wherein: The electrode active material is prepared by the preparation method according to any one of claims 1 to 23, and the electrode active material comprises: a core, containing ternary materials; The coating layer covers at least a portion of the surface of the core, and the coating layer contains a reaction product of a sulfur-containing compound and a lithium-containing compound, wherein the reaction product contains Li element, S element and O element.

25. The electrode active material according to claim 24, wherein The weight content of the S element in the electrode active material is 500-5000 ppm.

26. The electrode active material according to any one of claims 24 to 25, wherein The coating layer also contains one or more of the elements B, P and F; Under the condition of containing B element, the weight content of B element in the electrode active material is 500-3000ppm; Under the condition of containing P element, the weight content of P element in the electrode active material is 200-1500ppm; Under the condition of containing F element, the weight content of F element in the electrode active material is 500-3000 ppm.

27. The electrode active material according to any one of claims 24 to 25, wherein The electrode active material D V 50 The particle size is 1 to 25 μm.

28. The electrode active material according to claim 27, wherein The electrode active material D V 50 The particle size is 1 to 10 μm.

29. An electrode, wherein: Contains the electrode active material according to any one of claims 24 to 28.

30. A battery, wherein: Contains the electrode active material according to any one of claims 24 to 28.

31. A device comprising a battery, wherein: The device comprises the battery according to claim 30, wherein the battery serves as a power supply unit or an energy storage unit of the device.

32. The device according to claim 31, wherein The device is an electric device, and the battery is used to supply power to the electric device.

Citation Information

Patent Citations

  • Lithium ion battery and positive electrode material thereof

    CN108075111A

  • Positive active material for lithium secondary battery and methode of manufacturing the same

    CN111146441A